The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1121/1.423089
|View full text |Cite
|
Sign up to set email alerts
|

Sinuous instability of a planar air jet: Propagation parameters and acoustic excitation

Abstract: The sinuous instability wave of a planar air jet is excited by localized acoustic flow across the nozzle. Phase velocity and the growth exponent are found from synchronous hot-wire measurements made beyond the excited region, where the profile is approximately sech-squared. In the observed range of scaled radian frequency, 0.02-1.33 (the stability limit), results agree with real-frequency (spatially growing) analysis but not with complex-frequency (temporally growing) analysis. The latter predicts smaller phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…i v i v ac i; P VX ¼ hS w v ac Dp los i; (28) where h Á i indicates averaging over a period. The three contributions are plotted on Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…i v i v ac i; P VX ¼ hS w v ac Dp los i; (28) where h Á i indicates averaging over a period. The three contributions are plotted on Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This eigenvalue problem can be solved numerically for more realistic velocity profile 27 including the traditional Bickley profile. Nolle 28 conducted the resolution for a family of profiles:…”
Section: B Amplification and Convection Of Perturbations Of The Jetmentioning
confidence: 99%
“…The delay τ , introduced by the duration of convection of the initial perturbation η 0 along the jet, is related both to the distance W and to the convection velocity c v of transversal perturbations on the jet: τ = W cv . Both theoretical and experimental results [27,28,29] have shown that c v is related to the jet velocity itself through: c v ≈ 0.4U j .…”
Section: Amplification and Convection Of The Perturbations Along The Jetmentioning
confidence: 99%
“…Many of these questions can be settled only by detailed experiments such as those of Thwaites and Fletcher. The most recent studies by Nolle [29] sugupon the jet, the phase delay for propagation along the jet, and phase shift involved in the interaction of the jet flow with internal acoustic waves in the pipe. In total these must sum to 2π for the feedback loop to close.…”
Section: Transientsmentioning
confidence: 99%